2018
DOI: 10.3389/fnagi.2018.00302
|View full text |Cite
|
Sign up to set email alerts
|

Chlamydia pneumoniae: An Etiologic Agent for Late-Onset Dementia

Abstract: The disease known as late-onset Alzheimer’s disease is a neurodegenerative condition recognized as the single most commonform of senile dementia. The condition is sporadic and has been attributed to neuronal damage and loss, both of which have been linked to the accumulation of protein deposits in the brain. Significant progress has been made over the past two decades regarding our overall understanding of the apparently pathogenic entities that arise in the affected brain, both for early-onset disease, which … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
62
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 67 publications
(64 citation statements)
references
References 133 publications
(174 reference statements)
2
62
0
Order By: Relevance
“…Together, these findings support the "olfactory vector hypothesis"-that external agents entering the nasal cavity and damaging the primary olfactory nervous system and olfactory bulb constitute a basis for neurodegeneration [96,97]. A growing body of work has correlated pathogens with the development of neurodegenerative diseases including AD and PD [98][99][100][101][102][103][104][105][106][107][108]. One known case of post-melioidosis Parkinsonism has been described [109].…”
Section: Discussionmentioning
confidence: 58%
“…Together, these findings support the "olfactory vector hypothesis"-that external agents entering the nasal cavity and damaging the primary olfactory nervous system and olfactory bulb constitute a basis for neurodegeneration [96,97]. A growing body of work has correlated pathogens with the development of neurodegenerative diseases including AD and PD [98][99][100][101][102][103][104][105][106][107][108]. One known case of post-melioidosis Parkinsonism has been described [109].…”
Section: Discussionmentioning
confidence: 58%
“…Following the main tenet of the C. pneumoniae hypothesis, it was modeled that infected cells within these regions would cause Aβ plaque and NF tangle formation to form in the specified region. Since it has been found that immune response cells aggregate around areas where amyloid plaque formation by several studies [25,38], areas where microglia swarm an infected cell produces a single patch of plaque in the model. Since there is limited knowledge as to how tangle formation is initiated in a similar way, tangles are formed randomly in the model within the specified region.…”
Section: Model Rulesmentioning
confidence: 99%
“…The E4 allele of the APOE gene is currently the strongest risk factor for late-onset AD [46]. This gene, expressed extensively by astrocytes in the brain, encodes a protein component of the low-density lipoprotein (LDL) which transports cholesterol to neurons by binding to several cell surface receptors [25]. Studies have shown that AD patients with the E4 allele, which has also been implicated in the development of atherosclerosis and coronary heart disease, display significantly higher numbers of C. pneumoniae infected cells in affected brain regions compared to congruent samples from AD patients lacking the allele [47].…”
Section: Recommendations For Future Workmentioning
confidence: 99%
See 2 more Smart Citations